Digital PID based two-compensator for DC-DC converter - Furukawa, Yudai; Kurokawa, Fujio; Colak, Ilhami (Intelec, 2015)
The purpose of this paper is to present the performance characteristics of the digital PID based two-compensator for the dc-dc converter. Authors have already presented a fast PD control method, which can reduce the influence of the delay time. In this paper, the transient characteristics of output voltage are confirmed in the simulation when the sampling frequency of the PID control is slowed down. As a result, the tendency of the transient characteristics of output voltage is revealed. Therefore, the slower sampling frequency of PID control can be applied to the dc-dc converter compared with the conventional PID control.